Sự điều tra về thái độ của giáo viên và học sinh đối với việc học bằng phương pháp tra cứu qua mạng ở một trường phổ thông vùng sâu ở Vĩnh Long : - Đoàn, Thị Bích Điểm (Trường Đại học Cần Thơ, 2010)
The purpose of this study is to introduce Webquest to teachers and students in a rural high school in Vinh long to examine their attitudes towards the implementation of webquest in English class.